(untitled) (Impetus, 2021)
The purpose of this manuscript is to present the results of a research process related to the evaluation of personal and social values ​​in young soccer players between the ages of 10 and 13 from the city of Ibagué. For this, a validated instrument was used, which was the object of checking its reliability in advance. The findings found correspond to the existence of different tendencies and factors that affect the behavior of the child, which make it impossible to fully see the values ​​that characterize their early age; However, certain elements were revealed that manage to reveal an unquestionable pattern of behavior. The alternative answer for those subjects who are determined by unfavorable evaluative attitudes, would be represented in knowing primarily the causes that provoke their questionable types of behavior.